Trastornos respiratorios del sueño y su relación con la aparición de afecciones bucodentales en pacientes adultos: una revisión bibliográfica - Guamán Erique, Diana Mikaela (2024)
Sleep-related breathing disorders (SRBDs) are a group of conditions that interrupt normal breathing patterns, which can interrupt sleep and lead to various health complications, including oral health problems. The objective of this study is to identify the respiratory disorders that contribute to the development of oral diseases, to examine the specific oral health problems involved, and to analyze the relationship between these disorders and oral health. This study involved a thorough review of the available literature using databases such as PubMed, Scielo, Medline and Google Scholar. Sources are selected based on pre-defined inclusion criteria, and the PRISMA flow chart is used to filter and select relevant documents, resulting in 42 articles for analysis. The results are then summarized in tables, exploring the physiological and clinical relationships between sleep-related breathing disorders (SRBD) and various oral health conditions, with a focus on common risk factors. Furthermore, the analysis identified the following results: the most prevalent sleep-related breathing disorders include Obstructive Sleep Apnea, Central Sleep Apnea, Mixed Apnea, Central Hypoventilation Syndrome, and Upper Airway Resistance Syndrome. In addition, the oral health conditions that result from these disorders, based on their prevalence, are sleep bruxism, xerostomia, burning mouth syndrome, temporomandibular joint disorders, tooth erosion, muscular changes, tooth wear and periodontal disease. Consequently, this confirms that there is an association between these conditions. The study concludes that there is a significant correlation between sleeprelated breathing disorders and oral health conditions